13 PNEUMOCOCCAL SEPTIC ARTHRITIS AS THE INITIAL PRESENTATION OF MULTIPLE MYELOMA. (1st January 2006) - Sumrall, A.; Muzny, C.; Bell, J.; Dreiling, B.; Montgomery, G. V.
Abstract : Septic arthritis induced by Streptococcus pneumoniae is an uncommon manifestation of pneumococcal infection. Pneumococcus has been identified as the inciting pathogen in only 6% of cases of septic arthritis in recent retrospective studies. We report a case of polyarticular septic arthritis as the first manifestation of an underlying disease. Our literature review discloses that this is the first reported case of multiple myeloma initially presenting as pneumococcal septic arthritis in the United States and the second internationally. A 75-year-old black male with a past medical history of hypertension, adenocarcinoma of the prostate, osteoarthritis, diverticulosis, and dyslipidemia presented to the emergency department with a 3-day history of pain in the lower back, knees, hands, and feet that was atypical for his usual joint pain and was associated with subjective fevers and chills. Over the next 24 hours he became unable to stand independently. Physical examination revealed bilateral warm, erythematous knee joints with associated effusion. Significant laboratory showed a white blood cell count of 12, 700/μL, hematocrit of 29%, creatinine of 1.8 mg/dL, and a globulin fraction of 6.1 g/dL. Arthrocentesis produced grossly purulent fluid with microscopic diplococci. Four bottles of blood cultures grew Streptococcus pneumoniae . The patient began a 30-day course of intravenous ceftriaxone and received serial arthrocenteses. His renal function rapidly deteriorated with a rise in creatinine to 12.7 mg/dL over 5 days. Serum protein electrophoresis showed monoclonal IgG kappa gammopathy with quantitative IgG of 4, 640 mg/dL, and urine protein electrophoresis revealed an IgG kappa level of 16 mg/dL. No lytic lesions were seen on skeletal survey. Multiple myeloma was diagnosed and treatment was initiated with high-dose oral dexamethasone. The patient's renal function improved with hemodialysis and thalidomide was started. The patient had a good response to this therapy with decline in IgG level to 1, 070 mg/dL. In a review of 190 cases of patients with pneumococcal arthritis, 6% had underlying multiple myeloma. In this case, multiple myeloma was diagnosed promptly with rapid initiation of chemotherapy, which led to a more favorable outcome.